Investigating The English Speaking Skill Of The Eleventh Grade Students Of Smk Swasta 2 Tamansiswa Pematang Siantar By Using Tedxtalks Youtube channel - Mardin Silalahi; Natanael Saragih; Inggit Arimbi (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2023)
The aim of this research is to analyze the improvement of speaking skills by using the TEDxTalks YouTube Channel. The researcher carried out in class XI TKR 5 of the SMK SWASTA 2 TAMANSISWA PEMATANG SIANTAR. This research used the quantitative approach with an experimental design by using the one-group design by cluster sampling technique for choosing 32 students from class XI TKR 5 and every student would give the pre-test and post-test for data collection. The technique of collecting the data is by using the statistic application called SPSS 21.0 version. Based on the hypothesis testing, it is be shown that Tcounted = 65,000 > Ttable = 1,695 which indicates that the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. This statement means there is a significant differences on students’ speaking skill by using TEDxTalks YouTube Channel especially in their accuracy and fluency. The conclusion of this research is that the using of TEDxTalks YouTube Channel can significantly improve students' speaking skills, particularly accuracy and fluency